Siglec-G is a B1 cell-inhibitory receptor that controls expansion and calcium signaling of the B1 cell population - Hoffmann, Anja; Kerr, Sheena; Jellusova, Julia; Zhang, Jiquan; Weisel, Florian; Wellmann, Ute; Winkler, Thomas; Kneitz, Burkhard; Crocker, Paul R; Nitschke, Lars (Nature Immunology, 2007)
B1 cells are an important cell population for the production of natural antibodies and for antibacterial immunoglobulin responses. Here we identified the mouse protein Siglec-G as a B1 cell inhibitory receptor. Siglec-G was expressed in a B cell restricted way, with large amounts present in B1 cells. When overexpressed, Siglec-G inhibited B cell receptor-mediated calcium signaling. Siglec-G-deficient mice had massive expansion of the B1a cell population, which began early in development and was B cell intrinsic. Siglec-G- deficient mice had higher titers of natural IgM antibodies but not a higher penetrance of IgG autoantibodies. Siglec-G-deficient B1 cells showed a strongly enhanced calcium signaling. Our results demonstrate that Siglec-G-dependent negative regulation exists in B1 cells, which may explain the naturally muted signaling response of B1 cells.